Advancing sports science and physical education research through a shared understanding of the term motor performance skills: A scoping review with content analysis - Sortwell, A.; Behringer, M.; Granacher, U.; Trimble, K.; Forte, P.; Neiva, H. P.; Clemente-Suárez, V. J.; Ramirez-Campillo, R.; Konukman, F.; Tufekcioglu, E.; Filizn, B.; Branquinho, L.; et al. (International Journal of Kinesiology & Sports Science, 2022)
Background: The inappropriate usage of terms and concepts and/or unclear definitions provided in the scientific literature hinder progress in any scientific field. This risk is especially noticeable in applied fields of research such as sports science and physical education. Objective: This study explored existing literature that uses the term `motor performance skills` and aimed to propose a comprehensive definition to be applied in future research. Method: Following an adapted scoping approach grounded in the rapid review model, we searched electronic databases Pub-Med/Medline, Web of Science, and Scopus until February 2022. The primary demographic focus was sports science and physical education disciplines. After screening of titles and abstracts, 184 papers were identified for a full review. Twenty-two papers met the inclusion criteria from the full review and received qualitative content analysis. The qualitative content analysis focused on the elaborated qualities of the term `motor performance skill`. Coding was used to identify and extract content, identify patterns, and observe the depth of interpretation of the term. Results: Only six papers used descriptive language, and three used explanatory language to convey aspects of the term`s meaning. All included papers extrapolated or provided examples to demonstrate the term`s meaning. Based on a collaborative process, the study reached a proposed definition that has the potential to be coined for the term `motor performance skills` and used in future research. Conclusion: Thus, the current analysis revealed the need to collaboratively address the conceptual ambiguity and develop a comprehensive definition of `motor performance skills`